Bearing Capacity of Soft Soil Using Bamboo-Geotextile Composite - Khatib, Anwar (UIR Press, 2005)
Construction on soft clays is often affected by stability and settlement problems. General stabilization of these soils usually involves expensive soil improvement method in order to enhance stability suitably reducing the potential and prevailing uneven settlement. Studies on soft clay reinforced with bamboo-geotextile composite overlaid by granular layer had been carried out to determine the increase in bearing capacity of strip footing on the soft clay. The bamboos were arranged in square and parallel pattern having various ratio of distance (s) to width of footing (b), s/b = 3.0, 2.0, 1.0 and 0.5. The height of granular material (u) overlying the soft clay varies with u/b = 0.25, 0.50 and 0.75. The soft clay was made from kaolin slurry that was consolidated in square boxes of 600 mm width and 1000 mm height. The results show that there is a great increase in bearing capacity and decrease of settlement at failure for the reinforced model. The bearing capacity increment of more than 127 % was recorded for bamboos of square and parallel pattern, having the s/b = 0.50 at u/b = 0.25. However, bamboo arranged in square pattern gives better improvement of bearing capacity than the parallel pattern. It can be concluded that the bamboo-geotextile composite could be used as another alternative method in improving the bearing capacity of soft clay. This will therefore benefits the construction industry especially in highway engineering.